Global, regional and national mortality burden of laryngeal cancer attributable to occupational exposure to sulfuric acid and asbestos: 1990–2021 and projections to 2040 - Gong, Xin; Xu, Yinxia; Hao, Yong; Yi, Meitao; Yuan, Chao; Zheng, Zhenhong; Gong, Jia; Shen, Gongjie; Dong, Yongqi (Frontiers in Public Health, 2025)
BackgroundLaryngeal cancer (LC) is the most prevalent form of head and neck cancer, significantly impacting patients' health. Occupational exposure to sulfuric acid (OESA) and asbestos (OEA) is a recognized risk factor for LC, but the associated mortality burden remains unclear. This study aimed to evaluate the global trends of LC attributable to OESA and OEA, and to project future trends.MethodsBased on the Global Burden of Disease Study 2021, we analyzed the number of deaths, age-standardized death rates (ASDR), and estimated annual percentage changes by age, sex, and socio-demographic index (SDI) of LC attributed to OESA and OEA. Decomposition analysis was used to identify the drivers of disease burden changes. Frontier analysis was used to estimate achievable outcomes based on development levels. Additionally, Bayesian age-period-cohort model was used to predict future trends up to 2040.ResultsIn 2021, global LC deaths attributable to OESA and OEA were 3,612.35 (95% uncertainty intervals (UI): 1,504.31–6,492.29) and 3,392.00 (95% UI: 1,892.13–5,134.88), respectively, representing increases of 37.5% and 21.4%, respectively, from 1990. The ASDRs for OESA and OEA in 2021 were both 0.04 per 100,000 (95% UI: 0.02–0.07 and 0.02–0.06, respectively), both lower than in 1990. LC deaths attributable to OESA and OEA mainly occur in elderly patients, and men consistently showed higher LC deaths and ASDR than females. The ASDR for OESA was negatively correlated with the SDI, while OEA was positively correlated. Decomposition analysis highlighted differences in disease burden drivers across SDI regions. Frontier analysis showed that countries like Cuba and Pakistan were farthest from the OESA-related mortality burden frontier, while Monaco and Lesotho were farthest from OEA-related mortality burden. From 2022 to 2040, LC deaths attributable to OESA and OEA are projected to increase to 4,810.90 (95% UI: 1,628.04–8,010.74) and 3,648.48 (95% UI: 1,016.75–6,322.42), respectively.ConclusionsAlthough the ASDR decreased from 1990 to 2021, OESA and OEA remain contributors to LC mortality worldwide, with the number of deaths expected to increase over the next two decades. Disease burden varies significantly across SDI regions, suggesting that preventive measures should be tailored to specific SDI levels.